MOF-derived nanoporous carbons with diverse tunable nanoarchitectures - Kim, Minjun; Xin, Ruijing; Earnshaw, Jacob; Tang, Jing; Hill, Jonathan P.; Ashok, Aditya; Nanjundan, Ashok Kumar; Kim, Jeonghun; Young, Christine; Sugahara, Yoshiyuki; Na, Jongbeom; Yamauchi, Yusuke (Nature Publishing Group, 2022)
Metal-organic frameworks (MOFs), or porous coordination polymers, are crystalline porous materials formed by coordination bonding between inorganic and organic species on the basis of the self-assembly of the reacting units. The typical characteristics of MOFs, including their large specific surface areas, ultrahigh porosities and excellent thermal and chemical stabilities, as well as their great potential for chemical and structural modifications, make them excellent candidates for versatile applications. Their poor electrical conductivity, however, has meant that they have not been useful for electrochemical applications. Fortuitously, the direct carbonization of MOFs results in a rearrangement of the carbon atoms of the organic units into a network of carbon atoms, which means that the products have useful levels of conductivity. The direct carbonization of zeolitic imidazolate framework (ZIF)-type MOFs, particularly ZIF-8, has successfully widened the scope of possible applications of MOFs to include electrochemical reactions that could be used in, for example, energy storage, energy conversion, electrochemical biosensors and capacitive deionization of saline water. Here, we present the first detailed protocols for synthesizing high-quality ZIF-8 and its modified forms of hollow ZIF-8, core-shell ZIF-8@ZIF-67 and ZIF-8@mesostuctured polydopamine. Typically, ZIF-8 synthesis takes 27 h to complete, and subsequent nanoarchitecturing procedures leading to hollow ZIF-8, ZIF-8@ZIF-67 and ZIF-8@mPDA take 6, 14 and 30 h, respectively. The direct-carbonization procedure takes 12 h. The resulting nanoporous carbons are suitable for electrochemical applications, in particular as materials for supercapacitors.